Sistema híbrido de wetlands construídos no tratamento de esgotos sanitários - Patel, André Gustavo (2018)
In this study, the behavior of hybrid constructed wetlands were evaluated in the removal of carbonaceous, nitrogenous and phosphorous matter from sewage. Each system consisted in the combination of a vertical-flow constructed wetland followed by a horizontal-flow constructed wetland, one being vegetated (CW-P) with macrophyte (Eichhornia crassipes) and one system only with sand and gravel (CW-UP). These arrangements are henceforth called hybrid constructed wetland (CW). The systems operated in two stages: Stage I with HRT of 9 days and Stage II with HRT of 5 days, and kept at room temperature. The pH, temperature of the liquid, dissolved oxygen (DO), electrical conductivity (EC), oxidation-reduction potential (EH), Chemical Oxygen Demand (COD), total Kjeldahl nitrogen (TKN), total ammonia nitrogen (TAN), nitrite (N-NO2 - ), nitrate (N-NO3 - ), and phosphate phosphorus (P-PO4 -3 ) were determined in samples from the influent and effluent of each system. The wastewater used to feed the CWs was classified as ―week‖ sewage in terms of carbonaceous matter (COD) and ―medium‖ for TKN and P-PO4 -3 . The best removal efficiencies of COD (13.63 g m -2 d -1 ), PPO4 -3 (1.52 g m -2 d -1 ), N-NO2 - (0.01 g m -2 d -1 ) were verified in CW-P in Stage II with 83, 95, 80 and 52%, respectively; and TKN (5.46 g m -2 d -1 ) and TAN (4.42 g m -2 d -1 ) in Stage II with 73 and 88% in CW-P. The absorption of TN and TP by E. crassipes resulted in 11.77 and 10.37 g m -2 in the vertical unity and 6.12 and 6;92 g m -2 in the horizontal unity, with major role of the roots – 6.35 and 6.55 g m -2 in the vertical unity and 2.45 and 3.05 g m -2 in the horizontal unity, respectively. Removal of 4.65 and 5.59 logarithmic unities of thermotolerant coliforms were achieved in CW-P and CW-UP, respectively. For the incorporation of fibers from the macrophyte, it was possible to observe that the applied force to compressive stress (56 kN and 42 kN) was superior than the applied force to tensile stress. In the planted system a TN load of 1622.43 g m -2 was removed with plant contribution of 17.89 g m -2 , resulting in residual load of 82.21 g m -2 for the applied load of 1725.53 g m -2 ; and a PT load of 35.22 g m -2 was removed with plant contribution of 17.29 g m -2 , resulting in residual load of 170.33 g m -2 for the applied load of 222.87 g m -2 . Eichhornia crassipes had important role in the removal of nitrogen, varying in function of the operational conditions (applied loads and flow), depending also on the produced biomass.